A cooperative human-machine interaction warning strategy for the semi-autonomous driving context - Costa, Susana Raquel Pinto (2017)
This study is a part of an ongoing work regarding the possible scenarios during autonomous driving and it takes into consideration, not only academic literature and industry updates, but also the aspects described on the standards already disclosed. As autonomous driving systems become a more tangible reality, the development of an efficient warning strategy, within the human-machine interaction (HMI), is paramount, for a range of reasons that include the trust in these emerging systems. It has been noted by several researchers that a particular moment of the semi-autonomous driving is of special interest, which is the driver’s role shift from passive monitoring of the vehicle to active control of the autonomous driving system. This study presents a cooperative approach to the vehicle-driver communication strategy, accounting for both human factors and complexity of the AD systems. A nexus diagram has been developed that in a comprehensive way, provides an alternative strategy to the conventional static warning strategy, able to be customized in some specific traits, which can later be resorted to by programmers for expeditiously implementing this much needed strategy in the real context of semi-autonomous driving.